Public Debt, Public Investment and Economic Growth in Ghana (1980-2017) - Dor, Asiwome (KNUST, 2026)
A Thesis Submitted to the Institute of Distant Learning, Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the Requirement for the Degree of Master of Science in Economics